Condensed Tannins Improve Glycolipid Metabolism but Induce Liver Injury of Chinese Seabass (Lateolabrax maculatus) - Peng, Kai; Chen, Bing; Zhao, Hongxia; Wang, Yuxi; Huang, Wen (Frontiers in Marine Science, 2022)
A 63-day feeding trial with 640 juvenile L. maculatus was conducted to assess the effects of dietary CT on serum metabolites, antioxidant and immune response, liver histomorphology and glycometabolism enzyme activities of fish. Four diets were formulated to contain 0 (T1), 1 (T2), 2 (T3), and 2 g/kg of CT plus 4 g/kg of polyethylene glycol (PEG) (T4). PEG specifically binds with CT to neutralize CT activity. Fish were randomly distributed into 16 tanks (4 tanks per group and 40 fish per tank) and were fed to apparent satiation twice daily. Results indicated that fish fed T2 and T3 had lower (P<0.05) concentrations of serum albumin, total cholesterol and triacylglycerol, but higher (P<0.05) alanine aminotransferase activity than T1 and T4. T3 had lower (P<0.05) serum glucose but higher (P<0.05) insulin concentrations than other groups. Fish fed T2 and T3 had higher (P<0.05) liver superoxide dismutase, catalase, lysozyme and immune globulin M than T1 and T4. Compared with T1 and T4, hepatocytes in T2 and T3 were shown to have obvious vacuolar degeneration along with different degree of inflammatory cell infiltration. Fish fed T2 and T3 had higher (P<0.05) values of eosinophilic infiltrate and necrosis and greater (P<0.05) pyruvate kinase, but lower (P<0.05) glucokinase activities than those of fish fed T1 and T4. All parameters were similar (P>0.05) between T1 and T4. In summary, dietary CT up to 2 g/kg reduced serum lipid and glucose concentrations, enhanced liver antioxidant and immune response, improved glucose utilization but of L. maculatus. CT induced liver injury of L. maculatus which provided a caution for its application in aquaculture.